Possibilities and Obstacles Presented AI in Education by Learners PPKn at PGRI Wiranegara University - Cicilia Nur Anugrah; Ayu Maya Damayanti (Cendikia : Media Jurnal Ilmiah Pendidikan, 2026)
The use of Artificial Intelligence in higher education institutions brings several important issues, including the risks to student data privacy, concerns about ethics in AI model development, and the potential loss of human interaction in the learning process. This study aims to explore the opportunities and challenges of Artificial Intelligence, as well as the ethics of its use among PPKn students at Universitas PGRI Wiranegara. The study uses a descriptive qualitative method with a case study approach. The informants in this study were Civic Education students who met the criteria of having used AI, understanding the ethics of AI use, and understanding the opportunities and challenges that AI presents. The total number of informants in this study was 17, consisting of active Civic Education students from the 2022, 2023, and 2024 cohorts at Universitas PGRI Wiranegara. The results show that PPKn students see Artificial Intelligence as a tool that can help them in learning, but also as a tool that comes with challenges. AI brings both significant challenges and opportunities. A unique contribution of this study is the emphasis students place on using AI ethically in line with Pancasila principles. These findings show how important it is to use AI responsibly in learning for students as ethical digital users. Also, the findings suggest that Artificial Intelligence offers useful opportunities for learning, like helping students understand material and come up with ideas to complete assignments. However, Artificial Intelligence also comes with challenges and ethics are needed when using it